1991
DOI: 10.1093/oxfordjournals.alcalc.a045152
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Alcohol Ingestion on Whole Body and Muscle Protein Synthesis — A Stable Isotope Study

Abstract: The cause of the proximal myopathy associated with chronic alcohol ingestion has yet to be established. The clinical feature of muscle wasting implies either inhibited skeletal muscle protein synthesis, stimulated breakdown or a combination of both. Previous data suggest that breakdown is reduced, rather than promoted. This provides evidence, albeit indirect, that the myopathy is the result of inhibited muscle protein synthesis, which has been demonstrated recently in the rat model. We have examined the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…Our calculated S was found to be similar to the data described for healthy adults in the range of 3.0-4.0 g kg −1 day −1 [22,26]. However, only few results are available so far in the scientific literature on the effect of alcohol drinking on the protein turnover in humans [34][35][36][37]. Understandably, our findings are difficult to compare with the data of other studies since different groups of subjects, stable isotope-labelled tracer substances, methodologies, dosages, and units, respectively, were used.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our calculated S was found to be similar to the data described for healthy adults in the range of 3.0-4.0 g kg −1 day −1 [22,26]. However, only few results are available so far in the scientific literature on the effect of alcohol drinking on the protein turnover in humans [34][35][36][37]. Understandably, our findings are difficult to compare with the data of other studies since different groups of subjects, stable isotope-labelled tracer substances, methodologies, dosages, and units, respectively, were used.…”
Section: Discussionsupporting
confidence: 84%
“…Understandably, our findings are difficult to compare with the data of other studies since different groups of subjects, stable isotope-labelled tracer substances, methodologies, dosages, and units, respectively, were used. Pacy et al [34] examined the influence of alcohol intake on the fractional skeletal muscle protein synthesis in chronic alcoholics with a daily alcohol intake of at least 100 g for more than 10 years using the primed continuous infusion technique with l-[1-13 C]leucine. Assuming a leucine content of 8% of the whole-body protein, the converted S amounted to 3.23 g kg −1 day −1 and Downloaded by [134.117.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies with stable isotopes have shown that rates of skeletal muscle protein synthesis in alcohol misusers are lower than the rates seen in non-alcoholic control subjects (26). Animal studies also show that ethanol reduces skeletal muscle protein synthesis in acutely and chronically ethanol-dosed rats, though most studies have focused on the acute model.…”
Section: Animal Studies Of Alcohol Misuse and Effects On Protein Syntmentioning
confidence: 99%
“…Although the precise mechanism of the pathogenicity is unknown, a number of pathways have been proposed, including an increased generation of reactive oxygen species and disrupted membrane function (1,14). In skeletal muscle, as in other tissues, alcohol has been shown to promote a reduction in the fractional rate of protein synthesis (k s ) (17,23). There appears to be very little effect of alcohol on the rate of protein degradation, at least with acute alcohol treatment (10).…”
mentioning
confidence: 99%